2017
DOI: 10.1021/acs.biochem.6b01230
|View full text |Cite
|
Sign up to set email alerts
|

A Change in the Rate-Determining Step of Polymerization by the K289M DNA Polymerase β Cancer-Associated Variant

Abstract: K289M is a variant of DNA polymerase β (pol β) that has previously been identified in colorectal cancer. The expression of this variant leads to a 16-fold increase in mutation frequency at a specific site in vivo and a reduction in fidelity in vitro in a sequence context-specific manner. Previous work shows that this reduction in fidelity results from a decreased level of discrimination against incorrect nucleotide incorporation at the level of polymerization. To probe the transition state of the K289M mutator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(48 citation statements)
references
References 65 publications
4
41
0
Order By: Relevance
“…The steeper dihalogenated slopes for WT and I260M suggest that there is more sensitivity to charge stabilization during formation of TS in the presence of the dihalogenated analogues, which has been shown previously for WT pol β 2527 . This indicates that the dihalogenated dTTP analogues are either exposed to or stimulating the formation of an altered binding pocket as compared to the other analogues.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…The steeper dihalogenated slopes for WT and I260M suggest that there is more sensitivity to charge stabilization during formation of TS in the presence of the dihalogenated analogues, which has been shown previously for WT pol β 2527 . This indicates that the dihalogenated dTTP analogues are either exposed to or stimulating the formation of an altered binding pocket as compared to the other analogues.…”
Section: Resultssupporting
confidence: 75%
“…This variant loses the dependence of log( k pol ) on p K a4 observed with WT enzyme during correct incorporation but not during misincorporation, which pointed to a fundamental change in the RDS of K289M pol β relative to WT, with a shift to a step prior to chemistry 27 . Moreover, it was found that several of the dNTP analogues tested improved the fidelity of the K289M cancer-associated variant.…”
mentioning
confidence: 84%
“…In line with this, the Sweasy group has identified and characterized various functional POLB variants that have been implicated in the development of cancer (251)(252)(253)(254)(255). It was reported that POLB variants can be detected in up to 30% of human cancers (256).…”
Section: Dna Polymerase β (Polb)mentioning
confidence: 95%
“…Polβ has been reported to be mutated in 30% of a variety of human tumors such as lung, gastric, colorectal, and prostate cancer (37,38). Several of the cancer-associated polβ variants possess aberrant repair function in vitro such as a reduced fidelity stemming from impaired discrimination against incorrect nucleotide incorporation as reported for polβ cancer-associated mutant K289M (39,40). The expression of these variants in cells induces cellular transformation and genomic instability (4146).…”
Section: Introductionmentioning
confidence: 95%